Penyuluhan Kesehatan Mengenai Diabetes Melitus Dan Senam Kaki Diabetik Di Desa Karangjongkeng Kecamatan Tonjong Kabupaten Brebes - Ahmad Zakiudin (Lembaga Pengembangan Kinerja Dosen, 2021)
Diabetes Mellitus (DM) is a chronic disorder of the body's metabolism due to the hormone insulin in the body which cannot be used effectively in regulating blood sugar balance thereby increasing the concentration of sugar levels in the blood (hyperglycemia). The purpose of this study is to be able to understand diabetes mellitus and practice diabetic foot exercises in order to minimize tissue damage. Health education about diabetes mellitus and diabetic foot exercises can increase the knowledge of Karangjongkeng villagers to try their best to prevent more severe diabetes mellitus, namely tissue damage. Health education to residents can increase the knowledge and skills of diabetic foot exercises in preventing diabetes mellitus.